Prediction of rupiah exchange rate against Australian dollar using the Chen fuzzy time series method - Rahmawati, Rahmawati; Rahma, Ade Novia; Septia, Wiwik (Science, Technology and Communication Journal, 2021)
The exchange rate of the rupiah (IDR) to the Australian dollar is the price of one rupiah translated to the Australian dollar. Weakening or decreasing prices of the Rupiah to the Australian dollar are influenced by various factors, such as government policies and expectations. Therefore, the government or related parties must be careful in predicting the value of the rupiah exchange rate to the currency of the state, such as the Australian dollar. This report will discuss the prediction of the rupiah exchange rate to the Australian dollar for 223 days from December 2018 to July 2019 using the Chen fuzzy time series method. The results of this report are the prediction of the value of the exchange rate of the rupiah to the Australian dollar in December 2018 to July 2019 is be again in the interval 10,450 IDR to 10,920 IDR.